Studies towards the selective inhibition of β-alanine pathways in Mycobacterium tuberculosis - Koekemoer, Lizbe (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2006.